Geografia da música e representação social: estudo de caso de os Angueras - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This work aims to analyze and reflect on the musicalities acquired by Angueras – Grupo Amador de Arte. This artistic group was created in São Borja, in 1962. Throughout its trajectory, it became famous for singing the rivers of the region, especially Uruguay. We took as a basis for this work, two sound albums created by those involved, namely: Cantos de Pampa e Rio (1976) and Sinhá Querência (1994) To compose our reflections, we seek to present the socio-territorial development of São Borja and its surroundings. For the methodology, we present among the research techniques, the case study, the bibliographical research, interview, documental and content analysis. In terms of method, phenomenology was used. For the theoretical framework, we sought Cultural and Music Geography. Furthermore, it is understood that songs are social representations of reality. Among the members of the group, the notable figure of Apparício Silva Rillo, poet from Rio Grande do Sul, composer of works that are contained in this document, can be highlighted. As a result of our research, the texts present in the Angueras songs were related to analytical categories of Geography. Among them, we can highlight: geographic space, place, landscape, territory and region. Therefore, these concepts remained present in the songs we analyzed.
Keywords: Geografia cultural; Música; São Borja, RS – Geografia; São Borja, RS – História; Geografia; Os Angueras – Grupo Amador de Arte; Cultural geography; Music; CNPQ::CIENCIAS HUMANAS